South Sea Pearl Shell Quality Inspection Using X–Ray Digital Radiography - Bayu Suparta, G; Famelia Cerly, M; Christian Louk, A (KnE Life Sciences, 2019)
South sea pearl from Indonesia has been prominent in the sea pearl world market. The south sea pearls are produced from shells, Pinctada maxima ( Jameson, 1901). However, the quality of the south sea pearl of Indonesia commonly unspecified so that they are sold in bulk quantity to the world market. One of the problems is that due to lack of inspection technology access in order to define the sea pearl quality. The production of good quality sea pearls need a series of treatment for the shell. The process also takes a long time, about 2 yr to 3 yr. This paper presents in developing inspection technology using digital X-ray radiography and the way to define the dimension in correlation with its age. More specific is trying to distinguish the influence of culture period to the dimension of the sea pearl inside the shell. The existence of the sea pearl and its dimension are defined based on the digital radiography images. From the experiment, it is found the dimension of the sea pearl is dependent on the culture period. Keywords: Digital radiography, Pearls, Pinctada maxima ( Jameson, 1901), Quality control, X-ray inspection